2015
DOI: 10.1002/ps.4105
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of strigolactones, a strategic account

Abstract: Strigolactones (SLs) constitute a new class of plant hormones that have received growing interest in recent years. They firstly became known as signalling molecules for host recognition by parasitic plants, and for symbiosis of plants with arbuscular mycorrhizal fungi. Furthermore, they are involved in numerous physiological processes in plants, such as the regulation of plant architecture and the response to abiotic factors. SLs are produced by plants in extremely low quantities, and they may be unstable duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 65 publications
0
55
0
Order By: Relevance
“…CYP711A isoforms in red bell pepper, red clover, and pea plants may directly convert CL into orobanchol (5) or may convert CLA into orobanchol (5) with other oxygenases such as LBO after introducing the carboxyl group to CL by CYP711. The oxidation of C-18, the methyl group in the six-membered ring of CL, is likely to be required to form the B ring, as the oxidation of C-19 is required to form the C ring 20,31) (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…CYP711A isoforms in red bell pepper, red clover, and pea plants may directly convert CL into orobanchol (5) or may convert CLA into orobanchol (5) with other oxygenases such as LBO after introducing the carboxyl group to CL by CYP711. The oxidation of C-18, the methyl group in the six-membered ring of CL, is likely to be required to form the B ring, as the oxidation of C-19 is required to form the C ring 20,31) (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the commercially available ethyl ester auxins 14 and 15 were formylated using ethyl formate in the present of a base (NaH) in excellent yields and the resulting enols 16 and 17, respectively, were then coupled with chloro furanones 9-12 using potassium carbonate in DMF to afford hybrid-type SL analogues 18-25 in poor to very good yields (Scheme 2). In all cases, the yields of the products derived from auxin derivative 14 (18)(19)(20)(21) were higher than those of the counterparts of auxin derivative 15 (22)(23)(24)(25).…”
Section: Synthesismentioning
confidence: 83%
“…Several reviews cover the current state of affairs concerning the chemistry and bio-properties of SLs. [2][3][4][5][6][22][23][24] The availability of SLs is limited because levels of natural production are minute and their complete synthesis is quite laborious due to their complex structures. 25,26 Synthesis of simple bioactive analogues, having the same bioactiphore as natural SLs, has attracted considerable attention in recent years (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, scientists first explored structure-activity relationship of SLs (Zwanenburg and Pospisil, 2013). These studies showed that the α/β unsaturated system and D-ring of SL analogs are indispensable for their activity, while modifications of the ABCring impacted the level of their efficiency, as shown by testing the activity of the structurally less complex analogs GR5 and GR7 (Mangnus et al, 1992b;Zwanenburg et al, 2009Zwanenburg et al, , 2016c. Other simple analogs were developed by isosteric replacement leading to imino SL analogs (Kondo et al, 2007), CISA-1 (Rasmussen et al, 2013) and strigolactams (Lachia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%